The Relationship Between Risk Management, Non-Financial Performance Measurement, and Company Reputation in Integrated Reporting in State-Owned Banks in Indonesia - Maria Yovita R. Pandin; Achmad Bagas Djuan Rajendra; Salma Dewi Ambarsari; Salva Dewi Ambarwati; Fillah Ardhi (International Forum of Researchers and Lecturers, 2025)
This study looks at how integrated reporting (Y) is impacted by risk management (X1), non-financial performance (X2), and company reputation. The results of the first hypothesis test (H1) indicate that risk management (X1) significantly influences integrated reporting (Y) with a significance value of 0.634 (p>0.05). This means that the null hypothesis (H0) is rejected, indicating a significant contribution of X1 to Y. Conversely, the second hypothesis test (H2) shows that non-financial performance (X2) does not have a significant influence on integrated reporting (Y), with a significance value of 0.001 (p<0.05), so the null hypothesis (H0) is accepted and H2 is rejected. Similarly, the third hypothesis (H3) shows that corporate reputation (X3) does not have a significant effect on integrated reporting (Y) with a significance value of 0.000 (p<0.05), causing the null hypothesis (H0) to be accepted and H3 to be rejected. However, the simultaneous test (H4) reveals that risk management (X1), non-financial performance (X2), and company reputation (X3) collectively have a significant effect on integrated reporting (Y), as indicated by a significance level of 0.000 (p<0.05) and a calculated F value of 11.137, which is greater than the table F value of 3.443. This supports the acceptance of H4, indicating that although some variables are not significant individually, the combination of the three collectively contributes to explaining the variation in integrated reporting (Y).